Effects of excess dietary crude protein from soybean meal and dried distillers grains with solubles in diets for finishing pigs - S M Williams; C Feoli; S Issa; Terry L Gugle; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 2008)
A total of 180 pigs (90 barrows and 90 gilts, average initial weight of 148 lb) were used in a 67-d experiment to determine the effects of excess dietary CP on growth performance and carcass measurements in finishing pigs. The pigs were sorted by ancestry and blocked by weight with 12 pigs per pen and 5 pens per treatment. Treatments were corn-soybean meal-based diets formulated to 15.3 and 18.3% CP and a corn-soybean-DDGS-based diet formulated to 18.3% CP. Feed and water were consumed on an ad libitum basis until the pigs were slaughtered (average final weight of 282 lb) at a commercial abattoir. Pigs fed diets with high CP had lower (P<0.001) final weight, ADG, ADFI, and HCW, but these results were caused entirely by the diet with 40% DDGS. Our results indicated that diets with 40% DDGS decreased growth performance and economically important carcass measurements. However, the excess CP in those diets does not seem to be the culprit.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Carcass; Dried distillers grains with solubles; Finishing pigs; Growth; Protein